2018
DOI: 10.1002/adom.201800156
|View full text |Cite
|
Sign up to set email alerts
|

Strong SHG Response via High Orientation of Tetrahedral Functional Motifs in Polyselenide A2Ge4Se10 (A = Rb, Cs)

Abstract: and strong nonlinearity. However, these materials suffer from intrinsic drawbacks, such as low laser damage threshold and two-photon absorptions, which seriously limit their high-power applications. Therefore, new promising IR-NLO materials need to be discovered.Motivated by Chen's anionic group theory, [6] which states that NLO efficiency mainly originates from anionic groups, many NLO-active structure building units (NLO functional motifs) [7] have been developed over the past few decades, such as those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Recently, numerous experiments have shown that metal chalcogenides are abundant research resources for developing novel IR NLO materials due to their broad optical transparency and strong SHG responses derived from favorable covalent bonding characters. Specifically, the main-group-metal elements (e.g., Ga, In, Si, Ge, Sn) are often four-coordinated with chalcogen atoms to adopt asymmetric tetrahedral configurations, which are regarded as the typical “NLO active units” and play a very important role in achieving both noncentrosymmetric structures and strong SHG responses. In addition, enlarging the band gap is known as an effective strategy to overcome the most demanding problems of TPA and low LDT in IR NLO materials. Hence, the alkali or alkaline-earth metals without d–d or f–f electronic transitions have been taken into consideration in the tetrahedra-containing chalcogen system to improve the LDTs of NLO materials. The strategy has been confirmed by recently reported metal chalcogenides with large LDT, such as LiGaS 2 (11× that of AGS), BaGa 4 S 7 (3× that of AGS), Li 2 ZnSiS 4 (10× that of AGS), Li 2 BaGeS 4 (11× that of AGS), Ba 6 Zn 7 Ga 2 S 16 (28× that of AGS), Rb 10 Zn 4 Sn 4 S 17 (5× that of AGS), (K 0.38 Ba 0.81 )­Ga 2 Se 4 (13× that of AGS), Na 4 MgSi 2 Se 6 (9× that of AGS), Na 2 BaGeS 4 (8× that of AGS), Li 2 MnGeS 4 (40× that of AGS), and Na 2 Hg 3 Si 2 S 8 (4.5× that of AGS). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous experiments have shown that metal chalcogenides are abundant research resources for developing novel IR NLO materials due to their broad optical transparency and strong SHG responses derived from favorable covalent bonding characters. Specifically, the main-group-metal elements (e.g., Ga, In, Si, Ge, Sn) are often four-coordinated with chalcogen atoms to adopt asymmetric tetrahedral configurations, which are regarded as the typical “NLO active units” and play a very important role in achieving both noncentrosymmetric structures and strong SHG responses. In addition, enlarging the band gap is known as an effective strategy to overcome the most demanding problems of TPA and low LDT in IR NLO materials. Hence, the alkali or alkaline-earth metals without d–d or f–f electronic transitions have been taken into consideration in the tetrahedra-containing chalcogen system to improve the LDTs of NLO materials. The strategy has been confirmed by recently reported metal chalcogenides with large LDT, such as LiGaS 2 (11× that of AGS), BaGa 4 S 7 (3× that of AGS), Li 2 ZnSiS 4 (10× that of AGS), Li 2 BaGeS 4 (11× that of AGS), Ba 6 Zn 7 Ga 2 S 16 (28× that of AGS), Rb 10 Zn 4 Sn 4 S 17 (5× that of AGS), (K 0.38 Ba 0.81 )­Ga 2 Se 4 (13× that of AGS), Na 4 MgSi 2 Se 6 (9× that of AGS), Na 2 BaGeS 4 (8× that of AGS), Li 2 MnGeS 4 (40× that of AGS), and Na 2 Hg 3 Si 2 S 8 (4.5× that of AGS). …”
Section: Introductionmentioning
confidence: 99%
“…), and tetrahedral blocks (MQ 4 ) n − (M = Zn, Ga, Ge, etc. ; Q = S, Se). These acentric anionic motifs were frequently assembled into NCS structures with other cations. However, when incorporating strongly electropositive cations (alkali metal, alkaline-earth metal, or rare-earth metal), which usually form directionless ionic bonding interactions, acentric anionic motifs could be packed centrosymmetrically. , Another simple but effective strategy is transforming a parent centrosymmetric (CS) structure to an NCS one through structure modification methods, which shares the benefit of inheriting the NLO-functional motifs from the parent CS compounds in the target NCS ones.…”
mentioning
confidence: 99%
“…Among these units, versatile metal chalcogenides MQ 4 (M=Zn, Cd, Ga, In, and Ge; Q=S, Se), with a tetrahedral structure, are fundamentally NLO‐active functional motifs used to build IR NLO compounds . Strategies such as mixing different MQ 4 motifs, forming highly oriented tetrahedral arrays, and constructing supertetrahedral clusters and chains by modulating MQ 4 functional motifs, have been adopted to optimize SHG responses. Meanwhile, highly electropositive alkali or alkali‐earth metals were widely incorporated to widen band gaps, such as in BaGa 4 S 7 , Li 2 CdGeS 4 , and Na 2 BaGeS 4 …”
Section: Figurementioning
confidence: 99%